Fellow tribesmen : the image of native Americans, national identity, and Nazi ideology in Germany - Usbeck, Frank (Berghahn Books, 2015)
"Throughout the 19th and 20th centuries, Germans exhibited a widespread cultural passion for tales and representations of Native Americans. This book explores the evolution of German national identity and its relationship with the ideas and cultural practices around 'Indianthusiasm.' Pervasive and adaptable, imagery of Native Americans was appropriated by Nazi propaganda and merged with exceptionalist notions of German tribalism, oxymoronically promoting the Nazis' racial ideology. This book combines cultural and intellectual history to scrutinize the motifs of Native American imagery in German literature, media, and scholarship, and analyzes how these motifs facilitated the propaganda effort to nurture national pride, racial thought, militarism, and hatred against the Allied powers among the German populace"--Provided by publisher
Keywords: National characteristics, German -- History -- 20th century.; Nationalism -- Germany -- History -- 20th century.; Indians in popular culture -- Germany -- History -- 20th century.; Indians of North America -- Public opinion.; National socialism -- Philosophy.; Race -- Philosophy.; Popular culture -- Germany -- History -- 20th century.; Public opinion -- Germany -- History -- 20th century.; Germany -- Politics and government -- 1933-1945.; Germany -- Intellectual life -- 20th century.; Allemands -- Histoire -- 20e siècle.; Nationalisme -- Allemagne -- Histoire -- 20e siècle.; Peuples autochtones dans la culture populaire -- Allemagne -- Histoire -- 20e siècle.; Nazisme -- Philosophie.; Race -- Philosophie.; Culture populaire -- Allemagne -- Histoire -- 20e siècle.; Opinion publique -- Allemagne -- Histoire -- 20e siècle.; Allemagne -- Politique et gouvernement -- 1933-1945.; Allemagne -- Vie intellectuelle -- 20e siècle.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; HISTORY -- Europe -- Germany.; Indians in popular culture; Indians of North America -- Public opinion; Intellectual life; National characteristics, German; National socialism -- Philosophy; Nationalism; Politics and government; Popular culture; Public opinion; Race -- Philosophy; Germany; 1900-1999; History